Penerapan Teknik Peta Kehidupan Bermedia Foto dalam Pembelajaran Penyusunan Teks Deskripsi Siswa VII-C SMPN 1 Trowulan Tahun Pelajaran 2016/2017 - Pramuwibowo, Ariesta Bagus (Ta'allum: Jurnal Pendidikan Islam, 2016)
Here are various virtues of learning the description text for the seventh grade students, especially students of VII-C SMPN 1 Trowulan. First, an understanding of the description text is required so that students do not consider that the same description text with the text of the report on the observation. Second, learning compose the text of fiction in the novel, the structure of the text descriptions into one filler. Therefore, preparation of the text descriptions into something that must be understood by the students of VII-C SMPN 1 Trowulan. In addition to learning the primacy of the text, there is a map technique causes life with photo media should be applied in the preparation of instructional text description. First, psychologically, individuals experiencing different events that can be captured through photos. These events may be applied to various text, one text description. Second, map the life of the photo media is one way to visualize events that never happened clearly in your mind quickly. Based on the significance and cause of the research aimed to assess the accuracy of the activities of teachers and students as well as the thoroughness of learning outcomes on student learning preparation of the text description VII-C SMPN 1 Trowulan the academic year 2016/2017. This research uses experimental research design with quantitative descriptive method. Therefore, the data presentation in the form of pemerian or breakdown with numbers as supporting data. In addition, the data in this study were collected by the teacher activity assessment sheets, assessment sheets student activities, and student learning test result sheet. The results of this study as follows. First, the activity of teacher in the preparation of the text descriptions in class VII-C SMPN 1 Trowulan very appropriate because the activity score of 87. Second, the activities of students in the preparation of the description text in class VII-C SMPN 1 Trowulan appropriate because the activity score of 80. Third learning outcomes preparation of the text description of class VII-C SMPN 1 Trowulan complete because the average value of students was 74,81.